Design, Synthesis, and Antifungal Activity of Novel Benzimidazole Derivatives Bearing Thioether and Carbamate Moieties - Lei Yang (Journal of Chemistry)
In this study, a series of benzimidazole derivatives bearing thioether and carbamate moieties have been synthesized and evaluated for their in vitro antifungal activity against Cytospora mandshurica, Thanatephorus cucumeris, Botrytis cinerea, Verticillium daliae, Phytophthora infestans, and Gibberella zeae by the mycelium growth rate method. The result of bioassay demonstrated that most of the compounds had certain antifungal activity. Especially, compound E11 revealed better antifungal activity against Verticillium daliae and Phytophthora infestans at 50 μg/mL, with the inhibition rates of 70% and 75%, respectively, than those of albendazole (38% and 61%, respectively). To the best of our knowledge, it is the first study on the synthesis and antifungal activity of benzimidazole derivatives containing thioether and carbamate moieties.